Early Adolescent Substance Use and Mental Health Problems and Service Utilisation in a School-based Sample. (February 2019) - Brownlie, Elizabeth; Beitchman, Joseph H.; Chaim, Gloria; Wolfe, David A.; Rush, Brian; Henderson, Joanna
Objective: This paper reports on substance use, mental health problems, and mental health service utilisation in an early adolescent school-based sample. Method: Participants were 1, 360 grade 7 and 8 students from 4 regions of Ontario, Canada. Students completed an in-class survey on mental health and substance use. The sampling strategy and survey items on demographics, substance use, service utilisation, and distress were adapted from the Ontario Student Drug Use and Health Survey. Internalising and externalising mental health problems were assessed using the Global Assessment of Individual Needs – Short Screener. Distress was defined as fair or poor self-rated mental health. Results: Rates of internalising and/or externalising problems above the threshold exceeded 30%; yet, fewer than half had received mental health services in the past 12 mo. Substance use was associated with increased odds of internalising and externalising problems above the threshold and distress. Youth using cannabis had 10-times the odds of exceeding the threshold for internalising or externalising problems. The use of substances other than alcohol or cannabis was associated with increased odds of fair or poor self-rated mental health among grade 8 students. Of the youth who confirmed at least a substance use problem, most also reported mental health problems; this association was stronger among girls than boys. Conclusions: Early adolescent substance use was associated with concurrent self-reported mental health problems in a non-clinical sample. The low levels of service utilisation reported highlight the need for improved access to early identification and intervention to prevent the development of concurrent disorders.